ANTIOXIDANT AND CYTOTOXIC EFFECTS OF METHANOL EXTRACTS OF AMORPHOPHALLUS PAEONIIFOLIUS Ni - G, Karthika; Das, Archana; Santhy, Kumaran Sivanandan (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objectives: To identify the bioactive compounds present in Amorphophallus paeoniifolius and to evaluate the antioxidant and cytotoxic property of the plant extract. Methods: Preliminary phytochemical analysis was carried out by the standard method of Yadav and Agarwala [1]. Bioactive compounds were identified by GC – MS analysis. Antioxidant activity of the methanol extract were determined by two different methods viz., DPPH radical scavenging assay and reducing power assay. Also the extracts were tested for their ability to kill the proliferative cells (MCF-7) by MTT assay. Results: Ten pharmacology important compounds were identified by GC-MS analysis. Higher antioxidant potential of the extracts was observed in both assays. The appreciable free radical scavenging activity of the extracts might be attributed to the secondary metabolites like alkaloids, flavanoids, tannins, phenols and sterols present in the extract. The results of MTT assay indicated a significant growth inhibition at a low concentration of IC50 values (51.07µg/ml). Conclusion: Present study is an evidence to support the usage of the plant which possesses several antioxidant principles for medicinal uses. Keywords: Amorphophallus paeoniifolius, DPPH, reducing power, MCF-7 cells.